Black garlic exhibited hepatoprotective effect against monosodium glutamate-induced hepatotoxicity in animal model - Maulina, Nora; Zachreini, Indra; Gholib, Gholib; Suwandi, Abdulhadi; Akmal, Muslim (Narra J, 2024)
Monosodium glutamate (MSG) is commonly used as a flavor-enhancing agent in foods, and studies have demonstrated its toxic effects in animal models. Black garlic is known for its antioxidant and anti-inflammatory properties; however, there is a lack of studies on the potential hepatoprotective effect of black garlic ethanol extract (BGE) against MSG-induced hepatotoxicity in rats. The aim of this study was to investigate the hepatoprotective effects of ethanol extract of black garlic against MSG-induced liver damage in animal model. Twenty-five male Wistar rats were randomly assigned to five groups (n=5): negative control, MSG only, and MSG with three different doses of BGE. The MSG only and MSG with BGE groups were orally administered with 8 mg/kg MSG daily. After MSG treatment, the MSG with BGE groups received BGE orally at daily doses of 200, 400, or 600 mg/kg body weight for 16 consecutive days. Subsequently, the levels of serum liver enzymes aspartate aminotransferase (AST), alanine aminotransferase (ALT), interferon-gamma (IFN-γ), and cyclooxygenase-2 (COX-2) were measured. Our data indicated that the group treated with 200 mg/kg BGE had significant lower levels of AST and ALT significantly compared to the MSG-only group. The MSG-treated group had higher levels of the inflammatory markers COX-2 and IFN-γ, which were lowered by administration of 200 mg/kg BGE. In contrast, higher doses of BGE led to greater levels of COX-2 and IFN-γ compared to those in the MSG-only group. This study suggested that BGE might have hepatoprotective effects at low dose, potentially mitigating MSG-induced liver damage. However, the higher dose of black garlic extract did not alleviate inflammation, as shown by the higher levels of COX-2 and IFN-γ.